Cessation of contraction induces cardiomyocyte remodeling during zebrafish cardiogenesis - Yang, Jingchun (American Physiological Society, 2013)
Contraction regulates heart development via a complex mechanotransduction process controlled by various mechanical forces. Here, we exploit zebrafish embryos as an in vivo animal model to discern the contribution from different mechanical forces and identify the underlying mechanotransductive signaling pathways of cardiogenesis. We treated 2 days postfertilization zebrafish embryos with Blebbistatin, a myosin II inhibitor, to stop cardiac contraction, which induces a response termed cessation of contraction-induced cardiomyocyte (CM) enlargement (CCE). Accompanying the CCE, lateral fusion of myofibrils was attenuated within CMs. The CCE can be blunted by loss of blood in tail-docked zebrafish but not in cloche mutant fish, suggesting that transmural pressure rather than shear stress is accountable for the chamber enlargement. By screening a panel of small molecule inhibitors, our data suggested essential functions of phosphoinositide 3-kinase signaling and protein synthesis in CCE, which are independent of the sarcomere integrity. In summary, we defined a unique CCE response in genetically tractable zebrafish embryos. A panel of assays was established to verify the contribution from extrinsic forces and interrogate underlying signaling pathways.